Contrasting CO2 and water vapour fluxes in dry forest and pasture sites of central Argentina - Nosetto, Marcelo Daniel; Luna Toledo, Emanuel Santiago; Magliano, Patricio Nicolás; Figuerola, Patricia; Blanco, Lisandro Javier; Jobbagy Gampel, Esteban Gabriel (Wiley, 2020)
The dry forests of South America are a key player of the global carbon cycle and the regional water cycle, but they are being intensively deforested. We used eddy covariance measurements to compare the temporal patterns of CO2 and water vapour fluxes and their relationships with environmental variables in dry forest and pastures sites of central Argentina. Ecosystem fluxes showed clear contrasts in magnitude, timing and response to environmental controls between ecosystems. The dry forest displayed higher daily gross primary productivity (GPP, 10.6 vs. 7.8 g CO2 m−2 d−1) and ecosystem respiration (Reco, 9.1 vs. 7.0 g CO2 m−2 d−1) and lower net ecosystem exchange (NEE, −1.5 vs. −0.7 g CO2 m−2 d−1) than the pasture. These differences were explained by a lower tolerance of the pasture to cool temperatures and drought. The lowest NEE rates were observed between 26°C and 34°C in the pasture, but below this range, NEE increased sharply, switching to a carbon source with temperatures <20°C. By contrast, the dry forest remained as a strong carbon sink down to 18°C. The pasture also showed a stronger drop of GPP with drought compared with the dry forest, becoming a carbon source with soil wetness <25% of soil available water. Rainfall was strongly coupled with GPP in both ecosystems, but the dry forest responded to longer rainfall integration periods. This study helps to understand how ecosystems can respond to climate change, improve global scale modelling and increase the productivity and resilience of rangelands.